PENGARUH SELF-CONFIDANCE DAN RISK TAKING PROPENSITY TERHADAP INTENSI BERWIRAUSAHA (STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS NEGERI PADANG - Nelsy Yulia Syafitri; Elvi Rahmi (MANAJEMEN DEWANTARA, 2025)
Unemployment is still a serious problem that is difficult to overcome, many college graduates have difficulty finding work. They can take advantage of opportunities to create jobs with entrepreneurship, but prefer to look for work. This study was conducted to determine the effect of Self-Confidance and Risk Taking Propensity on Entrepreneurial Intention in students of the Faculty of Economics and Business, Universitas Negeri Padang. The type of research used is causative research with a quantitative approach. The population in this study were 1,574 students with a sample size of 95 students using proportional random sampling technique. The data collection technique was carried out through a survey using a questionnaire with a Likert scale. The variable indicators in this study consist of: Self-confidance variable (X1) indicators, (1) Facing failure, (2) Having mental readiness and skills (3) Optimistic about business success. Variable risk taking propensity indicators, (1) Decision making (decision making), (2) Courage to act (3) Able to bear losses / risks. Variable entrepreneurial intention indicators, (1) Desires, (2) Preferences, (3) Plans (4) Behaviour Expectancies. This instrument has passed the validity and reliability test, using multiple linear regression analysis method with SPSS version 25 which has passed the classical assumption prerequisite test, namely normality test, multicollinearity test and heteroscedasticity test, the hypothesis is then tested using the f-test, t-test, and coefficient of determination. The results of this study indicate that self-confidance and risk taking propensity affect entrepreneurial intention. This means that the higher the level of self-confidence and courage of students in taking risks, the higher their tendency to have intentions and plans in starting a business. Thus, strengthening psychological aspects such as self-confidence and the ability to face risks needs to be a concern in the development of entrepreneurship curriculum on campus in order to be able to produce graduates who are not only looking for work, but also able to create jobs.